The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1080/00288306.2002.9514959
|View full text |Cite
|
Sign up to set email alerts
|

Au‐Ag‐Hg and Au‐Ag alloys in Nokomai and Nevis valley placers, northern Southland and Central Otago, New Zealand, and their implications for placer‐source relationships

Abstract: Gold in Quaternary placers in the Nevis and Nokomai valleys is dominantly a-phase Au-Ag-Hg alloy (c.<10 wt% each of Ag and Hg) with subordinate Au-Ag alloy. The α-Au-Ag-Hg alloy is typically coarse grained (up to 2 cm), angular, and rarely flattened or folded. Crystalline texture, quartz intergrowths, and psuedo-hexagonal crystal pluck cavities are common. Fluvial transport distance estimates based on maximum flatness index of Au-Ag-Hg alloy particles are typically <10-20 km. Coarse (up to 2 cm) crystalline ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
8

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 34 publications
1
31
0
8
Order By: Relevance
“…Despite the potential usefulness of gold compositions for paragenetic studies of gold deposits in Otago, no data are yet available from hydrothermal veins. This lack of data has been highlighted by Youngson et al (2002) and Falconer (2003), who have identified geochemically distinctive Hg-rich placer gold (up to 10 wt% Hg) in deposits presumed to be derived from hydrothermally emplaced veins in the Otago Schist. Hence, knowledge of the mercury content of gold in Otago Schist hydrothermal veins has potential for linking placer deposits to sources, and determination of the geometry of paleodrainage systems.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Despite the potential usefulness of gold compositions for paragenetic studies of gold deposits in Otago, no data are yet available from hydrothermal veins. This lack of data has been highlighted by Youngson et al (2002) and Falconer (2003), who have identified geochemically distinctive Hg-rich placer gold (up to 10 wt% Hg) in deposits presumed to be derived from hydrothermally emplaced veins in the Otago Schist. Hence, knowledge of the mercury content of gold in Otago Schist hydrothermal veins has potential for linking placer deposits to sources, and determination of the geometry of paleodrainage systems.…”
Section: Introductionmentioning
confidence: 93%
“…These Hg-bearing alloys are thought to be hydrothermal in origin but no primary source for the gold has been found. The Hg-bearing gold is accompanied by abundant alluvial cinnabar in the Nevis and Nokomai valleys, and some primary genetic relationship between the cinnabar and Hg-bearing gold has been inferred (Youngson et al 2002). Cinnabar-bearing veins occur within basement rocks on the southwestern side of the schist belt ( Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It formed by the reworking of pre-Holocene material. Youngson et al (2002) have recorded such placers by residual concentration on the floor of the slowly incising valleys from New Zealand. The covariance of Mn and Ti in zone A is due to the presence of a significant amounts of pyrophanite (MnTiO 3 ) in the solid solution series with ilmenite (FeTiO 3 ) which is intergrown with rutile in the nigrine aggregates (Dill et al, 2006).…”
Section: Stages Iv-v: Colluvial-alluvial Placer and Duricrust II Formmentioning
confidence: 98%
“…Quantitative microprobe spot analyses were done using wavelength dispersion and a 5 ^m beam diameter. Mercury content of gold was determined using the data correction method described by Youngson et al (2002).…”
Section: Methodsmentioning
confidence: 99%